Sex, Politics, and Comedy The Transnational Cinema of Ernst Lubitsch - McCormick, Richard W. (Indiana University Press, 2020)
Ernst Lubitsch (1982-1947) was one of the most successful and influential German filmmakers in American film comedy. In this volume, Rick McCormick argues for a more transnational view of Lubitsch's career and films with respect to nationality, ethnicity, migration, class, sexuality, and gender. McCormick focuses on Lubitsch's Jewishness, which is inseparable from the distinct transnational character of the director, categorizing his early films as "Jewish comedies" where Lubitsch strikes a tenuous balance between Jewish humor, antisemitic jokes, stereotypes, and the incorporation of antifascist subjects into his popular films. Above all, the larger political issues at stake in Lubitsch's work are brought forward: German-Jewish perspectives and experiences, the subtle treatment of covert political and social messages, and the relationship of comedy, especially sexual comedy, to emancipatory politics and, in particular, to the turbulent politics of Europe and the United States in the first half of the twentieth century. The book discusses in depth the following films by Lubitsch: The Pride of the Firm (1914), Shoe Palace Pinkus (1916), Meyer From Berlin (1918), I Don't Want to Be a Man (1918), The Oyster Princess (1919), Madame Dubarry (1919), The Doll (1919), Sumurun (1920), The Wildcat (1921), The Marriage Circle (1924), The Student Prince in Old Heidelberg (1927), The Love Parade (1929), The Man I Killed (1932), Trouble in Paradise (1932), Design for Living (1933), Ninotchka (1939), The Shop Around the Corner (1940), and To Be or Not to Be (1942).